2010
DOI: 10.1111/j.1559-1816.2009.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

In the Eye of the Beholder: Differences Across Ethnicity and Gender in Evaluating Creative Work

Abstract: Creativity has been proposed as a supplement to ability tests as a way to reduce bias, as a result of the typical lack of ethnic or gender differences. Yet, creativity is usually measured through a consensus of rater judgment. Could there be implicit biases against people of different ethnicities or gender? This study examined stories and poems written by 205 students and rated by 108 different students. Females wrote poems that were judged to be more creative; there were no significant differences by ethnicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
40
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 35 publications
7
40
1
1
Order By: Relevance
“…but rather tended to rate White and female students as more creative than nonwhite and male students. This finding is consistent with past research examining unconscious gender and ethnicity biases in assigning slightly higher scores to White females (Eagly, Mladinic, & Otto, 1991;Eagly, Makhijani, & Klonsky, 1992;Kaufman, Baer, Agars, & Loomis, 2010;Kaufman, Niu, Sexton, & Cole, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…but rather tended to rate White and female students as more creative than nonwhite and male students. This finding is consistent with past research examining unconscious gender and ethnicity biases in assigning slightly higher scores to White females (Eagly, Mladinic, & Otto, 1991;Eagly, Makhijani, & Klonsky, 1992;Kaufman, Baer, Agars, & Loomis, 2010;Kaufman, Niu, Sexton, & Cole, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…These studies simply tried to distinguish female and male writing, without assessing quality, but the National Assessment of Educational Progress (also known as The Nation's Report Card) results clearly and consistently favors girls over boys in measures of fourth-, eighth-, and twelfth-grade writing skill (Baron, 2008;Salahu-Din, Persky, & Miller, 2008). J. C. Kaufman, Niu, Sexton, and Cole (2010) found that both men and women blindly rated female poetry as being more creative than male poetry (unlike in this study, J. C. Kaufman, Niu, et al, in press, did not reveal the gender or ethnicity of the writer).…”
contrasting
confidence: 72%
“…Theories of homosociability (Lipman-Blumen 1976, Kanter 1977, similarity (see overview in Byrne 1997) and the Goldberg paradigm (1968) were not confirmed through our experiment set. Results show no pro-male bias of men in the evaluation of the work, and are congruent with earlier research regarding creativity in other fields (Kaufman et al 2010) and advertising assessment of gender bias using students as judges (Sego 1999, Windels et al 2010, Roca et al 2012. They are also very similar to the results of the gender-bias research in other fields using name cues (Olian et al 1988, Swim et al 1989, and Eagly et al 1992.…”
Section: Discussionsupporting
confidence: 79%